Human bone regeneration from wood: a novel hierarchically organised nanomaterial. (3rd December 2012) - Finardi, Ugo; Sprio, Simone
The case of a novel biomimetic material for bone regeneration is studied. The growing costs of bone-related diseases (mainly due to the ageing of world population) and the quest for better life conditions spur the research for novel materials able to mimic and regenerate human bone subsequent to traumas. Natural structures (such as wood) are considered the best starting material for this purpose. The case of a totally new material, produced via a complex chemical-physical procedure starting from rattan wood, is analysed in its implications both on the technical-scientific and on the managerial-commercial side. The novel material has been implemented in a patented invention protecting a novel device for bone substitution. A SWOT analysis completes the case study, together with conclusions on its features.